Diposide based high-frequency ceramics - Alekseev Yu. I.; Vasil'ev E. P.; Reznitskii L. Z.; Shatalov P. I.; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (1987, 1987)
В фонде НТБ ТПУ отсутствует